The answer would be B because the sum of the squares of the 2 shorter sides equal the square of the longer side, which is the pythagoream theorem of a^2+b^2=c^2.
Answer:
C
Step-by-step explanation:
Answer:
Step-by-step explanation:
z
Answer:
![\frac{(6p+14)}{p}](https://tex.z-dn.net/?f=%5Cfrac%7B%286p%2B14%29%7D%7Bp%7D)
Step-by-step explanation:
![(p+\frac{7}{3})(\frac{6}{p})](https://tex.z-dn.net/?f=%28p%2B%5Cfrac%7B7%7D%7B3%7D%29%28%5Cfrac%7B6%7D%7Bp%7D%29)
Making denominator same in first bracket we get
![(\frac{3p+7}{3})(\frac{6}{p})](https://tex.z-dn.net/?f=%28%5Cfrac%7B3p%2B7%7D%7B3%7D%29%28%5Cfrac%7B6%7D%7Bp%7D%29)
![(\frac{(3p+7)*6}{3*p})](https://tex.z-dn.net/?f=%28%5Cfrac%7B%283p%2B7%29%2A6%7D%7B3%2Ap%7D%29)
Dividing 6 by 3 we get 2
![(\frac{(3p+7)*2}{p})](https://tex.z-dn.net/?f=%28%5Cfrac%7B%283p%2B7%29%2A2%7D%7Bp%7D%29)
using distributive law
![(\frac{6p+14}{p})\\](https://tex.z-dn.net/?f=%28%5Cfrac%7B6p%2B14%7D%7Bp%7D%29%5C%5C)
Hence this is our answer